Effectiveness of Cognitive Behavioral Therapy and Muscle Relaxation on Fasting Blood Sugar Levels among Type 2 Diabetes Mellitus: A Systematic Review - Meylani Anaabawati Anaabawati; Hotma Rumahorbo; Rr. Sri Endang Pujiastuti (International Journal of Nursing and Health Services (IJNHS), 2021)
Diabetes mellitus type 2 is a metabolic disease in the form of a collection of symptoms due to an increase in blood sugar. Interventions cognitive behavioral therapy and muscle relaxation focused on reducing fasting blood sugar levels shown to affect the management of diabetes mellitus. This literature study aimed to evaluate cognitive-behavioral therapy's effectiveness and muscle relaxation on fasting blood sugar levels in people with type 2 diabetes. This search systematic review was conducted with PRISMA using the electronic database method Science Direct, Proquest, PubMed, Scopus, Springer Link. The research study criteria used a randomized control trial, quasi-experimental, experimental, meta-analysis review published in 2015-2020. Based on 27 literature studies that found muscle relaxation intervention effectively controlling glycemic and lowering blood sugar levels. The study results were significant in muscle relaxation, improving blood sugar levels, and found multiple outcomes such as anxiety, depression, and quality of life. Cognitive-behavioral therapy and muscle relaxation can be applied to control and reduce blood sugar levels and improve the quality of life of people with type 2 diabetes mellitus